Arbuscular mycorrhizal fungi and phosphorus supply on seedlings of mangabeira - Costa, Cynthia Maria Carneiro; Cavalcante, Uided Maaze Tiburcio; Goto, Bruno Tomio; Santos, Venézio Felipe dos; Maia, Leonor Costa (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate the effects of the association of arbuscular mycorrhizal fungi (AMF) and phosphorus fertilization on seedlings of "mangaba" (Hancornia speciosa). The experiment, at a greenhouse, was in a completely randomized factorial design with two treatments of the native soil from an H. speciosa orchard, fumigated with methyl bromite and non-fumigated, six doses of P (3*, 3, 48, 93, 138 and 183 mg dm-3) and three inoculation treatments, Gigaspora albida Schenck & Smith, Glomus etunicatum Becker & Gerdemann and an uninoculated control, with four replicates. The treatment 3* did not receive nutrient solution and the others received Hoagland nutrient solution without phosphorus, at the time of inoculation. After 150 days, high increment on height, shoot biomass and leaf area were observed in the treatments with G. albida, in fumigated soil. Positive response to inoculation occurred in seedlings cultivated in soil with the lower phosphorus level, in both soil treatments. Hancornia speciosa was mycorrhiza dependent only when in fumigated soil, at the lowest phosphorus level. In treatments at other levels, the dependency varied according to the AMF and soil condition. The association with G. albida enhanced growth of H. speciosa.